2007
DOI: 10.1557/jmr.2007.0318
|View full text |Cite
|
Sign up to set email alerts
|

Enhance plasticity of bulk metallic glasses by geometric confinement

Abstract: We report that bulk metallic glasses (BMGs) with large plasticity can be obtained in conventional brittle BMGs by a shrink-fit metal sleeve. The mechanical performance especially the plasticity in the Zr41.2Ti13.8Cu12.5Ni10Be22.5 BMG with a shrink-fit copper sleeve is much enhanced. The approach results in the formation of the highly dense and frequent interacting and arresting events of shear bands and is the origin of the observed large global plasticity. The results present another simple step toward toughe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
21
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 30 publications
1
21
0
Order By: Relevance
“…In 2007, Li et al firstly deposited a Ni-15% Fe coating on the surface of a Zr-based BMG by electroplating, and the compression plasticity of the deposited BMG was improved from about 1.1% to~2.0% [23]. Yu et al used Cu tubes as geometric constraints to improve the plasticity of a Zr-based BMG, hereafter, the surface modification strategy was often called geometric constraint method [27]. Following similar strategy, Qiu et al used electroplating to coat Zr-based BMG with Cu coating, and found that the thicker coating shows greater toughening effect [28].…”
Section: Introductionmentioning
confidence: 99%
“…In 2007, Li et al firstly deposited a Ni-15% Fe coating on the surface of a Zr-based BMG by electroplating, and the compression plasticity of the deposited BMG was improved from about 1.1% to~2.0% [23]. Yu et al used Cu tubes as geometric constraints to improve the plasticity of a Zr-based BMG, hereafter, the surface modification strategy was often called geometric constraint method [27]. Following similar strategy, Qiu et al used electroplating to coat Zr-based BMG with Cu coating, and found that the thicker coating shows greater toughening effect [28].…”
Section: Introductionmentioning
confidence: 99%
“…The present technique is particularly effective for producing cylindrical non-crystalline/crystalline composite (sandwich) structures. It is expected that such structures would exhibit attractive mechanical properties in contrast to monolithic metallic glasses, as indicated by Chen et al [36] and Yu et al [37].…”
mentioning
confidence: 99%
“…A compressive strain as large as 80% for a previously brittle BMG was obtained under constrained conditions, by tuning the strain rate and aspect ratio [13]. Large plasticity has also been obtained by shot-peening [16], electrodeposition [17,18] and use of a metal sleeve [19]. Very recently it has been…”
mentioning
confidence: 99%
“…So to enhance the plasticity of BMGs, it is necessary to promote the activation of multiple shear bands [2][3][4][5][6][7][8][9][10] and hinder the localization and rapid propagation of shear bands [11][12][13][14][15][16][17][18][19]. Indeed much important progress has been made in enhancing the ductility of BMGs by various ways [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19], such as by introducing second phase particles on the nanoscale/microscale [2][3][4][5] or solid solution particles [6] which restrict the severe localization and rapid propagation of shear bands, the as-prepared BMG composites could exhibit a global plasticity of about 7% [7].…”
mentioning
confidence: 99%
See 1 more Smart Citation